Comparison of EUS-guided conventional smear and liquid-based cytology in pancreatic lesions: A systematic review and meta-analysis - Chandan, Saurabh; Mohan, Babu P.; Khan, Shahab R.; Ofosu, Andrew; Dhaliwal, Amaninder S.; Shah, Aun R.; Bhogal, Neil; Mashiana, Harmeet S.; Mashiana, Simran S.; Kassab, Lena L.; Ponnada, Suresh; Facciorusso, Antonio; Bhat, Ishfaq; Singh, Shailender; Witt, Benjamin L.; Adler, Douglas G. (Endoscopy International Open, 2020)
Background and study aims Endoscopic ultrasound (EUS)-guided fine-needle aspiration (EUS-FNA) has limitations of inadequate sampling and false-negative results for malignancy. It has been performed using conventional smear (CS) cytology with rapid on-site evaluation (ROSE) with reasonable diagnostic accuracy. An alternative to ROSE is liquid-based cytology (LBC). Commonly used LBC techniques include precipitation-based (SurePath™) and filtration-based (ThinPrep®, CellPrep®). Data regarding the diagnostic efficacy of LBC compared with CS are limited.Methods Multiple databases were searched through March 2020 to identify studies reporting diagnostic yield of EUS-guided CS and LBC in pancreatic lesions. Pooled diagnostic odds and rates of performance for the cytologic diagnoses of benign, suspicious, and malignant lesions were calculated. Diagnostic efficacy was evaluated by pooled rates of accuracy, sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV). Results Nine studies with a total of 1308 patients were included in our final analysis. Pooled diagnostic odds of CS cytology were 1.69 (CI 1.02–2.79) and 0.39 (CI 0.19–0.8) for malignant lesions when compared to filtration-based and precipitation-based LBC techniques, respectively. For CS, precipitation-based and filtration-based LBC, pooled diagnostic accuracy was 79.7 %, 85.2 %, 77.3 %, sensitivity was 79.2 %, 83.6 %, 68.3 %, and specificity was 99.4 %, 99.5 %, 99.5 %, respectively. Conclusions The precipitation-based LBC technique (SurePath™) had superior diagnostic odds for malignant pancreatic lesions compared with CS cytology in the absence of ROSE. It showed superior accuracy and sensitivity, but comparable specificity and PPV. Diagnostic odds of CS cytology in the absence of ROSE were superior to the filtration-based LBC technique (ThinPrep®, Cellprep®) for diagnosing malignant pancreatic lesions.